Deskripsi Tingkat Ideasi dan Risiko Bunuh Diri Berdasarkan Revised-Suicide Ideation Scale (R-SIS) pada Remaja (Journal of Telenursing (JOTING), 2025)
This study aims to describe the level of suicidal ideation and risk in adolescents based on the Revised Suicide Ideation Scale (R-SIS) instrument. Suicide is one of the leading causes of death in adolescents worldwide, and early detection of suicidal ideation and risk is essential for effective prevention. The method used is quantitative descriptive research. The sample in this study was 250 adolescents aged 14–19 years who were selected using a purposive sampling technique. Data was collected using the validated Revised-Suicide Ideation Scale (R-SIS) questionnaire. Data analysis was carried out univariately to describe the frequency and percentage distribution of each category of suicidal ideation and risk. The results showed that 62.8% of respondents were female, and 52.8% of respondents had suicidal ideation in the mild category. As many as 44% of respondents showed passive ideation (covert suicidal desire), while 46% showed active and structured ideation (overt resolved plans and preparations). These findings emphasize the importance of early detection and a comprehensive assessment approach to both forms of suicidal ideation in efforts to prevent suicide in adolescents. Keywords: Suicidal Ideation, Mental Health, R-SIS, Adolescents, Suicide Risk